Personal and familial history of single parents and their coping strategies. - Granada, Yrene Kai L. (2001.)
This descriptive study aims to find out the socio-demographic characteristics of single parents, the factors that contributed in their becoming a single parent, and their coping strategies. (p)Five (5) unwed single mothers of the University of the Philippines in the Visayas were the respondents of this study. Three (3) came from the Miag-ao campus and two (2) from Iloilo City campus. Data was gathered by the use of an unstructured interview guide purposively constructed by the researcher. The ways of Coping Scale by Lazarus and Folman (1985) was also used in determining the specific coping strategies of the respondents. (p)The results showed that the ages of single parents are between 20-24 years. Their family size ranges from two to four members. Except for one who is a Protestant, the rest of the respondents are Catholic. All respondents got pregnant while still in college aging 20 years and below. All except for one, who is on leave of absence are enrolled at the University of the Philippines in the Visayas at the time of the study. (p)The respondents identified various interacting factors that they believe to have contributed on their becoming a single parent. These can be categorized into three: personal, environmental, and economic. The personal factors include their specific views and attittudes, which are liberal attitude towards pre-marital sex and high regard for single parents. The environmental factors include the respondents' family, friends, and school environment. Of the familial factors, the respondents mentioned the following: perceived lack of care and affection from their families, inadequate sense of belonging and lack of guidance from their parents. The respondents felt some pressure to engage in pre-marital sex as most of their friends are doing it. The liberal atmosphere in school has reinforced the respondent's own liberal attitude and their decision to be a single parent. Most of the respondents' parents do not want their daughters to get married due to financial instability or state of unemployment of the biological fathers. (p)The most frequently used coping strategy of single parents is seeking meaning, with the highest mean score 3.62. Seeking meaning, an emotion-focused strategy, describes effort by respondents to create positive meaning in their lives after giving birth by focusing on personal growth.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP in the Visayas, Miagao, Iloilo
Keywords: Single Parents -- Coping Strategies